Sanghaya 2001 Philippine arts and culture yearbook. (National Commission for Culture and the Arts, 2001)
This Yearbook is a record of the artistic and cultural output of the year 2000 which ought to serve as a reference guide for historians and cultural planners. It contains article reviews and comments on the activities and achievements of Filipino visual artists, dancers, writers, musicians, filmmakers,architects, theater artists, media practitioners and heritage advocates.